Genetic diversity and population structure analyses using hypervariable microsatellite markers in foxtail millets (Setaria species): future smart nutri-cereal crop - Reddy, M.P.; Rai, V.P.; Reddy, C.V.; Kumar, R.; Paliwal, R.; Sinha, B. (2025)
Knowledge of genetic diversity in germplasm resources is a prerequisite for crop improvement and successful breeding programs. Foxtail millet (Setaria species), a staple food in certain regions, stands out for its rich content of carbohydrates, proteins, dietary fiber, and essential minerals, contributing to a well-balanced diet. The genetic diversity and population structure of a foxtail millet collection consisting of 107 accessions were measured using 31 class I hypervariable SSR markers (>24 bp). 106 polymorphic alleles were detected, ranging from 2 to 8 alleles per locus, across the entire collection with an average of 3.42 alleles per locus. The average polymorphism information content (PIC), gene diversity (GD) and major allelic frequency (MAF) were 0.49, 0.56 and 0.53, respectively. Unweighted neighbor-joining based cluster analysis classified all the genotypes into four distinct major clusters I, II, III and IV, with 25, 40, 21 and 21 genotypes, respectively. Pair-wise estimates of dissimilarity values ranged from 0.094 to 0.931, with a mean of 0.719. The population structure analysis categorized the entries into four sub-populations, namely SP1, SP2, SP3 and SP4, which have 44, 26, 22, and 15 accessions, respectively. The standardized population distance (Fst) within the populations ranged from SP1 (0.604) to SP4 (0.207) with an average Fst of 0.384. The present study identified eight genotypes based on their genetic distance and favorable phenotypic traits for potential use in future breeding programs. These genotypes include four accessions of Setaria italica (ISe 1387, ISe 1234, ISe 1286, ISe 375), one accession of Setaria viridis (GS 40), one accession of Setaria faberi (SIA 2745), and two landraces (SC 13685 and SC 13653). The genetic insights presented in this study are valuable for the utilization of foxtail millet germplasm in future breeding endeavours.